Mapping cognitive translation and interpreting studies: A bibliometric approach - Olalla-Soler, Christian; Franco Aixelá, Javier; Rovira-Esteva, Sara (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article identifies the specific characteristics of Cognitive Translation and Interpreting Studies (CTIS) as a branch of Translation and Interpreting Studies (TIS), adopting a bibliometric approach. The main data source for this study was the Bibliography of Interpreting and Translation (BITRA), which – as at September 2019 – included more than 77,000 TIS records, covering the diversity of languages and document types used in TIS research. BTRA is the only TIS database to feature citing information. CTIS-related records were analysed, and those published between 1976 and 2015 were compared with the whole corpus of TIS research output for the same period – again, as registered in BITRA. Specifically, we analysed: (a) the general features and evolution of CTIS publications over time (by thematic co-occurrence, by title content words, by format and by language); (b) authorship, focusing on co-authorship and on the most productive authors; (c) the citation patterns of CTIS documents, including a brief analysis of its most cited authors and publications; and (d) CTIS accessibility through a study of the ratio of documents published in open access. These aspects were analysed both synchronically and diachronically so as to describe CTIS as a whole and to identify any changes over time. Our results yield a first overview of CTIS from a bibliometric perspective and provide a methodological point of departure for future bibliometric studies in this area.